The Tyrrhenian section of San Giovanni di Sinis (Sardinia): stratigraphic record of an irregular single high stand. Rivista Italiana di Paleontologia e Stratigrafia - LECCA, LUCIANO; CARBONI S. (2007)
A new analysis of the most representative Upper Pleistocene (Tyrrhenian, MIS 5e) section of San Giovanni di Sinis (Oristano, Sardinia) has provided a more detailed genetic stratigraphy of a low wave energy beach and temperate lagoon up to emerged peri-lagoonal facies deposits. These peri-lagoonal facies contain remains of fossil vertebrates, which, though few and fragmentary, bear witness to an at least temporary freshwater palaeoenvironment and the presence of deers and terrapins. Besides, the stratigraphy of this outcrop shows shoreface-backshore sandstones overlaying an erosion surface cut on the vertebrate-bearing layers. Facies analysis and sequence stratigraphy of the succession have provided support to a new eustatic interpretation significance. In fact, there appears to be evidence of one irregular single eustatic highstand, rather than two eustatic peaks as previously believed. The facies evolution and the local stratigraphic disconformities are interpreted as being associated with a lateral shift of the depositional environment within the same system formed during the MIS 5e sea level variations. As sea water level continued to rise so an erosional unconformity, caused by wave ravinement, formed between the low wave energy beach-lagoon sequence and the successive wave dominated beach facies sequence. This interpretation is supported by comparison with other sections of the Tyrrhenian in western Sardinia. The maximum sea level attained during the Tyrrhenian stage is a clear indication of a warm-temperate climate which can be correlated to the well known orbital interglacial configuration when the eustatic signal of Greenland's ice sheet melting occurred.